Reccurent Hemorrhage after Pancreatoduodenectomy: Report of a Case Successfully Managed with Operative Hemostasis - Sasajima, Koji; Miyamoto, Masayuki; Uchida, Eiji; Tajiri, Takashi; Hiroi, Makoto; Nakamuara, Yosiharu; Yamamura, Susumu; Yokoyama, Tadashi; Egami, Kaku; Fukuhara, Munehisa (Nihon Fukubu Kyukyu Igakkai Zasshi (Journal of Abdominal Emergency Medicine), 2003)
The patient was a 59 years old man, who was diagnosed as having cancer of the head of the pancreas, and a pancreatoduodenectomy was performed. The postoperative course had been uneventful until shock caused by intra-abdominal hemorrhage occurred on the 16th postoperative day. At laparotomy, a causative injury of the common hepatic artery was found, and it was repaired. Re-bleeding occurre 11 days after the second surgery, however, and the third surgery was performed. The bleeding locus was the same as the previous one, and it was fixed with a transfixing ligation of the common hepatic artery since the vascular wall was severely damaged. Postoperatively, mild impaired liver function was seen, but it recovered within 3 weeks. The patient was discharged on the 88th day from the initial surgery.